Weight gain of Progestin and Combined Contraceptive Users - Handayani, Tinuk Esti; Suharto, Agung (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
Weight gain of Progestin and Combined Contraceptive Users